Metabolic Energy of Action Potentials Modulated by Spike Frequency Adaptation - Yi, Guo-Sheng; Wang, Jiang; Li, Hui-Yan; Wei, Xi-Le; Deng, Bin (Frontiers in Neuroscience, 2016)
Spike frequency adaptation (SFA) exists in many types of neurons, which has been demonstrated to improve their abilities to process incoming information by synapses. The major carrier used by a neuron to convey synaptic signals is the sequences of action potentials (APs), which have to consume substantial metabolic energies to initiate and propagate. Here we use conductance-based models to investigate how SFA modulates the AP-related energy of neurons. The SFA is attributed to either calcium-activated K+ (IAHP) or voltage-activated K+ (IM) current. We observe that the activation of IAHP or IM increases the Na+ load used for depolarizing membrane, while produces few effects on the falling phase of AP. Then, the metabolic energy involved in Na+ current significantly increases from one AP to the next, while for K+ current it is less affected. As a consequence, the total energy cost by each AP gets larger as firing rate decays down. It is also shown that the minimum Na+ charge needed for the depolarization of each AP is unaffected during the course of SFA. This indicates that the activation of either adaptation current makes APs become less efficient to use Na+ influx for their depolarization. Further, our simulations demonstrate that the different biophysical properties of IM and IAHP result in distinct modulations of metabolic energy usage for APs. These investigations provide a fundamental link between adaptation currents and neuronal energetics, which could facilitate to interpret how SFA participates in neuronal information processing.